Oviposition deterrent and ovicidal activity of three edible oils (black seed, sesame and soybean oils) against puls beetle, Callosobruchus chinensis (Lin.) (Coleoptera: Bruchidae) on green gram, Vigna radiata (Bangladesh Journal of Zoology, 2019)
The effectiveness of three different edible oils - black seed (Nigella sativa), sesame (Sesamum indicum) and soybean (Glycene max) was evaluated for the control of pulse beetle, Callosobruchus chinensis on green mung pulse, Vigna radiata. The oviposition deterrent and ovicidal activity of these three oils were compared between fresh mung pulses and pulses treated at different doses (1, 3 and 6 μl). The results indicated that the rate of oviposition and the mean number of emerged adults of C. chinensis on mung pulses treated with black seed, sesame and soybean oil were lower than their respective control pulses. The lowest number of eggs were recorded in soybean oil treated seeds (13.8 ± 1.07, 12.6 ± 1.36, 10.0 ± 1.82) followed by sesame (51.8 ± 4.63, 25.8 ± 8.52, 14.2 ± 4.50) and black seed oil (67.2 ± 9.71, 27.4 ± 5.52, 21.0 ± 5.54) at dose 1 μl, 3 μl and 6 μl, respectively in order. Soybean oil at the rate of 6μl/50 seeds was significantly effective (10.0 ± 1.82) to inhibit egg deposition. In case of ovicidal activity, minimum number of adults were emerged from black seed oil treated pulses (25.2 ± 2.73, 24.2 ± 0.58, 22.4 ± 1.17 at dose 1, 3 and 6 μl, respectively). Black seed oil at the rate of 6μl/ 50 seeds was the most effective (22.4 ± 1.17) than other edible oils.Bangladesh J. Zool. 47(1): 59-65, 2019